Construction of Yeast Recombinant Expression Vector Containing Human Epidermal Growth Factor (hEGF) - Jamal Mohammadian (Advanced Pharmaceutical Bulletin, 2013)
Purpose: The objective of this study was construction of recombinant hEGF-pPIC9 which may be used for expression of recombinant hEGF in following studies. Methods: EGF cDNA was purchased from Genecopoeia Company and used for PCR amplification. Prior to ligation, the PCR product and pPIC9 vector was digested with EcoRI and XhoI and ligated in pPIC9 vector and subjected to colony PCR screening and sequencing analysis. Results: PCR amplification of EGF cDNA using recombinant hEGF-pPIC9 vector as template was concluded in amplification of 197bp fragment. Construction of recombinant hEGF-pPIC9 of EGf gene was verified by PCR and sequencing. Conclusion: Construction of Recombinant hEGF-pPIC9 was the primary stage for production and expression of EFG in the future study.